Analysis of Laminar Forced Convection of Air for Crossflow Over Two Staggered Flat Tubes - Tahseen, Tahseen Ahmad; M., Ishak; M. M., Rahman (Universiti Malaysia Pahang, 2012)
In this work, the numerical simulation of steady heat transfer and fluid flow over a bank of flat tubes in staggered configurations for determining the constant surface temperature is presented. The results are attained using the finite volume method (FVM) and body fitted coordinates (BFC) technique. Transverse ratios (ST/Ds) of the pitch to small diameter of 3.0, 4.0 and 6.0 are also considered. The Reynolds numbers used are 10, 20, 60, 80 and 100, and the Prandtl number is taken as 0.7. The isothermal line, streamline and average Nusselt number were analyzed in this paper. It was found that the strength of the heat transfer between the surface of the tubes and the air flow increases with increasing Reynolds number and increasing pitch-to-diameter ratios. Also, the effect of the Reynolds number clear for the isothermal line, streamline and the average Nusselt number.